Digital Dystopia - Tirole, Jean (American Economic Review, 2021)
Autocratic regimes, democratic majorities, private platforms, and religious or professional organizations can achieve social control by managing the flow of information about individuals’ behavior. Bundling the agents’ political, organizational, or religious attitudes with information about their prosocial conduct makes them care about behaviors that they otherwise would not. The incorporation of the individuals’ social graph in their social score further promotes soft control but destroys the social fabric. Both bundling and guilt by association are most effective in a society that has weak ties and is politically docile. (JEL D64, D72, D83, D91, K38, Z13)